Report on the scientific results of the Norwegian expedition to Novaya Zemlya 1921 - Norske Novaja Semlja edspedisjon, 1921; Holtedahl, Olaf, 1885-; Norske videnskaps-akademi i Oslo; Norway. Statens forskningsfond; Norske Novaja Semlja Ekspedisjonen (1921) (Kristiania (Oslo) A. W. Brøggers boktrykkeri a/s, 1924)
Mode of access: Internet.